Sustainable Banking Performance in Indonesia: An Updated Conceptual Paper - Eko Tama Putra Saratian; Usep Suhud; Hamidah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores sustainable banking performance in Indonesia, emphasizing the integration of environmental, social, and governance (ESG) principles within banking practices. Employing a mixed-method approach, the research combines a systematic literature review and a preliminary survey of 125 respondents. The literature review synthesized global and local studies, identifying key frameworks, challenges, and opportunities, with a particular focus on Indonesia’s regulatory and socio-economic context. The survey revealed significant public awareness of sustainable finance, with respondents familiar with the concept. However, gaps were identified, particularly in the awareness of specific initiatives like interest subsidies for electric vehicle financing. These findings underscore the critical role of regulatory alignment, stakeholder engagement, and innovation in driving sustainability efforts. Additionally, the study highlights opportunities for Indonesian banks to align with global standards such as the Principles for Responsible Banking, while addressing barriers like organizational inertia and resource constraints. This research provides actionable insights for policymakers, practitioners, and scholars, contributing to the theoretical and practical advancement of sustainable banking in Indonesia